Si la leche es blanca, ¿Por qué el queso es amarillo? - Escobar Zapata, Carlos Alfonso (2021)
Cow's milk, which is used to make cheese, contains b-carotene, which is the compound responsible for the natural pale-yellow color of cheese. This yellow-orange colored compound is found naturally in the grass that cows feed on. As it is fat soluble, it is stored in the cow´s fat and passes into the milk encapsulated inside the so-called fat globules contained in milk. Since these globules scatter the incident light, milk appears to be white. During cheese making, these fat globules break down, releasing the b-carotene, which stains the cheese with its characteristic yellow color. Currently, to homogenize the cheese color in the industry, Annatto is added, a natural colorant extracted from the plant Bixa orellana L., present in the Peruvian Amazonia.